The freedoms of religion and culture under the South African constitution: do traditional African religions enjoy equal treatment? - Amoah, Jewel; Bennett, Tom (Journal of Law and Religion, 2008)
On Sunday, January 20, 2007, Tony Yengeni, former Chief Whip of South Africa's governing party, the African National Congress (ANC), celebrated his early release from a four-year prison sentence by slaughtering a bull at his father's house in the Cape Town township of Gugulethu. This time-honored African ritual was performed in order to appease the Yengeni family ancestors. Animal rights activists, however, decried the sacrifice as an act of unnecessary cruelty to the bull, and a public outcry ensued. Leading figures in government circles, including the Minister of Arts and Culture, Pallo Jordan, entered the fray, calling for a proper understanding of African cultural practices. Jody Kollapen, the Chair of the Human Rights Commission, said: “the slaughter of animals by cultures in South Africa was an issue that needed to be dealt with in context. Cultural liberty is an important right. …” That the sacrifice was defended on the ground of African culture was to be expected. More surprising was the way in which everyone involved in the affair ignored what could have been regarded as an event of religious significance. Admittedly, it is far from easy to separate the concepts of religion and culture, and, in certain societies, notably those of pre-colonial Africa, this distinction was unknown. Today in South Africa, however, it is clearly necessary to make such a distinction for human rights litigation, partly because the Constitution specifies religion and culture as two separate rights and partly because it seems that those working under the influence of modern human rights seem to take religion more seriously than culture.
free
Keywords: Africa.; Christianity and African religions; Culture and religion; Islam and African religions; Law enforcement; Rio Grande Valley (Colo-Mexico and Tex); South Africa – Religion